The woman and her inner dialogue: How Positive Psychotherapy transforms psychosomatic challenges into strength - Elena Drazheva; Stiliyana Stamova (The Global Psychotherapist)
This article presents the case of a patient with endometriosis and related reproductive difficulties who sought support through positive psychotherapy to cope with the emotional and physical challenges of her health condition. Applying the Five Fingers method, the therapist works with the patient to build a positive internal dialogue and accept vulnerability as a strength. Through this approach, the patient recognizes and makes sense of her emotions, needs, and internal conflicts, turning difficulties into a stimulus for personal development. The case study highlights the importance of an empathic and structured therapeutic approach when dealing with psychosomatic symptoms. It demonstrates the potential of positive psychotherapy to support patients in processing traumatic experiences. The article offers a useful model for clinical work with patients suffering from chronic illness and points to new perspectives for coping and personal growth.